A Study on the Effect of Teachers' Technological Teaching Styles on Students' Learning Behavior: A Case Study in Buddhist Sunday School - Ventiana Murti; Juni Suryanadi; Sandjaja Dharmatanna; Susanto Susanto; Luwiha Luwiha; Rina Manggalani; Sidartha Adi Gautama (Universitas Sebelas Maret, 2024)
Teaching style is the most essential factor in the implementation of learning. Learning is not merely a transfer of knowledge but also a process of shaping individuals to think critically, independently, and responsibly. This study aims to examine the influence of technological teaching styles of Buddhist Sunday school teachers on the learning behaviour of Sunday school students. The research was conducted at Buddhist Sunday schools in Pringsewu Regency. This study uses a quantitative approach with a survey method, and data processing is done using SPSS 16. The population in this study consists of 66 Buddhist Sunday school students. The results show that the technological teaching style of Buddhist Sunday school teachers has a positive and significant effect on the learning behaviour of Sunday school students in Pringsewu Regency. It emphasizes that the technological teaching style is one component in shaping students' learning behaviour; however, external factors also play an essential role in developing learning behaviour. The results of this study have a significant impact on the context of shaping students' learning behaviour. It can be applied in the Buddhist Sunday School environment in Pringsewu Regency, where students are encouraged to be more active and independent in the technology-based learning process.